Incidencia de los factores competitivos en la gestión de aguas y vertimientos de la curtiembres pedraza en el barrio San Benito: estudio de caso (2018)
The tanneries in the San Benito neighborhood have gone through many difficulties to function, the environmental problems and the lack of competitiveness are factors that affected the growth and sustainability of many companies in the sector. To comply with the environmental regulations added to market pressures, some tanneries sought access to cleaner and more sustainable production through new processes, access to technology, training of employees, handling of environmentally friendly chemicals, etc., which favored the efficient use of water and generated a lower pollutant discharge in water sources, allowing in turn to obtain the wastewater discharge permit necessary to operate legally. This article aims to analyze how the initiatives of water and wastewater management besides contributing in the environmental aspect, can affect the competitiveness of tanneries, for this purpose an investigation is made in the Pedraza Tannery that has the wastewater discharge permit with others who also have it, where it is possible to determine both the benefits and the disadvantages that affect the creation of competitive advantages that favor the growth of companies in the sector.